ANALISA KESELARASAN INDIKATOR TUJUAN PEMBANGUNAN BERKELANJUTAN DENGAN RANCANGAN PERATURAN DAERAH KABUPATEN INDRAGIRI HILIR TENTANG RENCANA PEMBANGUNAN JANGKA MENENGAH KABUPATEN INDRAGIRI HILIR PERIODE 2019 – 2023 - Hikmatul Hasanah, Rosliana, Akbar Alfa (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
The Indonesian Government's commitment to achieving the Sustainable Development Goals (SDGs) is seen in the Republic of Indonesia Presidential Regulation Number 59 of 2017 on the Implementation of SDGs Achievement which provides a mandate to integrate SDGs into the development agenda. At present Indragiri Hilir Regency is drafting a Regional Regulation Plan on the Subnational Mid-Term Development Plan. This study can be a reference in the preparation of the SDGs Regional Action Plan. The findings of this study are 18 Harmonized Indicators and 26 Proxy Indicators.